Review of New Circumstances of Adjuducation, that Has Entered Into Legal Force - N. V. Klyaus (Сибирское юридическое обозрение, 2020)
The article discusses the procedural issues of reviewing, under new circumstances, a court decision that has entered into legal force on the basis of the legal position of the Constitutional Court of the Russian Federation. The study is based on the norms of the Civil Procedure Code of the Russian Federation and the Code of Administrative Procedure of the Russian Federation, as well as the positions of the Supreme Court of the Russian Federation. The experience of courts in this category of cases is given. Violation by the courts when considering civil cases based on statements by interested parties of a legally established procedure for judicial proceedings is critically evaluated.